2022
DOI: 10.1590/0037-8682-0575-2021
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Chagas disease: from pathophysiology to clinical practice

Abstract: Despite substantial progress toward its control, Chagas disease continues to be a major public health problem in Latin America and has become a global health concern. The disease affects approximately 6 million people, of whom 20-40% will develop cardiomyopathy over the years after the initial Trypanosoma cruzi infection. Chagas cardiomyopathy is the most serious and frequent manifestation of Chagas disease. Clinical manifestations vary widely according to the severity of myocardial dysfunction, ranging from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(73 reference statements)
1
7
0
2
Order By: Relevance
“… 474 , 866 Ademais, as empíricas condutas terapêuticas sugeridas quando de sua formulação 364 idealmente deverão ser lastreadas em estudos aleatorizados de comprovação de eficácia. 474 , 866 , 867 …”
Section: Condutas Para Prevenção E Tratamento De Complicações Tromboe...unclassified
See 1 more Smart Citation
“… 474 , 866 Ademais, as empíricas condutas terapêuticas sugeridas quando de sua formulação 364 idealmente deverão ser lastreadas em estudos aleatorizados de comprovação de eficácia. 474 , 866 , 867 …”
Section: Condutas Para Prevenção E Tratamento De Complicações Tromboe...unclassified
“… 474 , 866 In addition, the empirical therapeutic managements suggested by the time it was formulated 364 should be ideally supported by randomized studies of efficacy. 474 , 866 , 867 …”
Section: Managements To Prevent and Treat Thromboembolic Complicationsmentioning
confidence: 99%
“…Even though the pathophysiological mechanisms are not completely understood, clinical approaches for the prevention of stroke in CD are demanded. 123 Interestingly, in a long-term follow-up benznidazole therapy was associated with a decreased incidence of CD progression from the IND to the CARD form, and with a reduced risk of cardiovascular events, including stroke. 124 Considering the putative effect of benznidazole on biological mechanisms contributing to stroke, our studies in chronically T. cruzi -infected mice showed that benznidazole therapy abrogated atrial fibrillation and reduced the expression of chemokines and cytokines (such as CCL3, TNF, and IFNγ) in the cardiac and the systemic inflammatory profile, as decreased the TNF and nitric oxide serum levels.…”
mentioning
confidence: 97%
“…Indeed, stroke is an important neurobehavioural change in CD, leading to chronic disabilities. 121 , 122 , 123 Although most strokes are cardioembolic, related to apical aneurysm, mural thrombus, and atrial fibrillation, small vessel diseases and atherosclerosis may also concur to stroke in CD patients. Thus, endothelial dysfunction, and prothrombotic and inflammatory disorders may represent non-embolic risk factors for stroke in CD.…”
mentioning
confidence: 99%
See 1 more Smart Citation